Urban Ataxia:CY - Timotheou,Nataly (2019)
Over the last four decades, the extended usage of cars for the daily mobility of people inwards and outwards the city of Limassol has taken over a huge part of the public space and formed a nature of urban ataxia (lack of order).Environmental pollution, social isolation, cultural stall and economical failure have become collateral consequences, at increasing rates and at high cost to all living beings. With an obligation to reach European standards and address climate change issues, the government of Cyprus has put the city of Limassol under the study of a sustainable urban mobility plan which which looks into introducing alternative mobility infrastructures to relieve the city from the monopolist usage of cars. This condition will surface the opportunity of developing an urban skin which ought to bridge the past ataxia to the future taxis (order). Through the main arteries of the city, friction shall occur in more than one way among the traveling agents and evolve in qualitative and quantitative aspects; one of the essential steps would be to generate sustainable public spaces. Alongside this radical reformation of the city, crucial trigger points can enable these new spaces if appropriately developed, in order to contribute to the blossoming of a bottom up livable city.
Keywords: Cyprus; Limassol; Parametric Design; Bottom Up; Livable city; Walkability; Urban Design; Public realm; Architecture; Disorder; Order